Novel mutation in the periaxin gene causal to Charcot–Marie–Tooth disease type 4F. Issue 2 (October 2020) - Chen, Yu-hui; Zhang, Hua; Meng, Ling-bing; Tang, Xiao-yan; Gong, Tao; Yin, Jian
Charcot–Marie–Tooth (CMT) disease is the most common hereditary neuropathy. Mutations in the periaxin gene ( PRX ) can cause CMT type 4F, an autosomal recessive neuropathy, which is clinically characterized by slowly progressive distal muscle atrophy and weakness, with pes cavus deformity of the foot, and the absence of deep tendon reflexes. To date, dozens of reports of PRX mutations have been published worldwide, but none have been reported in Chinese patients. Here, we describe a 14-year-old Chinese boy with neuropathy characterized by slowly progressive limb weakness and atrophy, as well as sensory ataxia, whose cerebrospinal protein levels were 1627 mg/L. Genetic analysis identified a novel homozygous mutation, c.1174C>T (p.R392X), in exon 6 of PRX, which is the first case of its kind recorded in China.